Investigation Into Deformation and Failure Characteristics of the Soft-Hard Interbedded Rock Mass Under Multiaxial Compression - Li, Ang; Shao, Guojian; Li, Yaodong; Sun, Yang; Su, Jingbo; Liu, Juncheng (Frontiers in Earth Science, 2022)
The influence of loading path, intermediate principal stress and weak layers on the deformation property and failure characteristics of soft-hard interbedded rock mass is initially discussed in this study. First, the laboratory experiments of multiaxial compression failure are carried out to soft-hard interbedded rock samples of Jinping. Three failure modes of rock samples caused by different distribution forms of weak layers under uniaxial compression and deformation property and failure characteristics of rock samples in different loading paths under biaxial compression are analyzed. Then, considering the property of strain softening, numerical models are established based on the elastic-brittle-plastic constitutive relation. The effect of weak layer dip angle, quantity, distribution form, and volume ratio on strength characteristics is further investigated. The results reveal that the failure mode of Jinping soft-hard interbedded rock samples generally follows the pattern of multi-fracture splitting under uniaxial compression, and the pattern of tension-shear damage under biaxial compression. The intermediate principal stress is positively correlated with the vertical failure loading. The number of weak layers has no significant effect on the “U” type strength characteristics of samples. However, as the number of weak layers increases, there is a tendency for the minimum of vertical failure loading to move forward in the direction of smaller dip.